AL amyloidosis: an overview on diagnosis, staging system, and treatment - Morè, Sonia; Manieri, Valentina Maria; Corvatta, Laura; Morsia, Erika; Poloni, Antonella; Offidani, Massimo (Frontiers in Hematology, 2024)
Systemic light-chain (AL) amyloidosis is a monoclonal plasma cell disease characterized by the deposition of amyloidogenic monoclonal light-chain fragments in organs, causing their dysfunction. Clinical manifestations could be very aspecific, but the most frequent ones are proteinuria with or without renal failure or heart failure, with the kidney and the heart being the first two involved organs. Histological diagnosis with Congo red staining is the gold standard, but typing the amyloid with immunohistochemistry or mass spectrometry of the Congo red positive tissue is necessary to establish if an AL or ATTR amyloidosis could be diagnosed. Staging AL amyloidosis before treatment could help physicians to prognosticate the disease. Recently, staging systems were set separately for different involved organs, using biomarkers. Autologous stem cell transplant after a daratumumab-based induction treatment is the cornerstone of therapy in younger and fit patients, with the goal of reaching a deep and rapid disease hematological and organ response. Novel therapies, borrowed from a therapeutical model of multiple myeloma, are studied to optimize AL amyloidosis outcomes. In this review, we make an overview of diagnostic procedures, staging system, and therapies of AL amyloidosis.